Effects of Top Management Team Characteristics on Patent Strategic Change and Firm Performance - Zhou, Yongtao; Zhou, Yi; Zhang, Li; Zhao, Xu; Chen, Weijing (Frontiers in Psychology, 2022)
Patent strategy is increasingly recognized as a vital contributor in promoting enterprise core competitiveness. Top management team (TMT) has been indicated as one of the key factors driving changes in patent strategy. Based on upper echelons theory, this study examines how TMT characteristics, namely team diversity, emotional intelligence and safety climate, influence enterprise patent strategic change, and hence, the business outcome. Data from 930 top managers in 228 enterprises showed that the changes in patent strategies are significantly influenced by top manager characteristics. These aforementioned internal TMT factors have diverse effects on the speed and scope of enterprise patent strategic change, which in turn affect firm performance in a positive and negative way respectively.